2015
DOI: 10.1002/eji.201545585
|View full text |Cite
|
Sign up to set email alerts
|

Systemic IL‐12 burst expands intestinal T‐lymphocyte subsets bearing the α4β7 integrin in mice

Abstract: The intestinal immune system is complex and displays unique anatomic and functional characteristics. Numerous immune cell subsets are located beneath the epithelial barrier and their activity is highly regulated. Using hydrodynamic shear of IL-12 cDNA to achieve systemic expression of IL-12 in mice, we evaluated the effect of a transient burst of this cytokine on the activation status of T cells from Peyer's patches (PPs), mesenteric lymph nodes (MLNs), and colonic lamina propria (LP). Following systemic IL-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…3). It is well known that IL-12 is the major cytokine for Th1 cell differentiation 68, 69 . In response to inflammations, both monocyte-derived DCs and macrophages produce IL-12 7072 .…”
Section: Discussionmentioning
confidence: 99%
“…3). It is well known that IL-12 is the major cytokine for Th1 cell differentiation 68, 69 . In response to inflammations, both monocyte-derived DCs and macrophages produce IL-12 7072 .…”
Section: Discussionmentioning
confidence: 99%
“…(a), analysis of the gene expression array showed the fold changes of the inflammatory cytokines in livers between WT and FCN‐A KO mice. Recently, in the same way, Pedrotti et al . demonstrated that systemic cytokines could impair DSS colitis by priming lymphocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, isotretinoin induced an anti-inflammatory immune cell profile in vitro and in vivo [21,28]. Pedrotti et al described local intestinal effects on lamina propria cells after systemic changes of IL-12 levels [40]. Thus, it is tempting to speculate that the previously described decrease of systemic IL-12p40 levels is affecting local IECs by up-regulating IL-12rb1 through a negative feedback mechanism that has been described for IL-7/IL-7R on T-cells [41,42].…”
Section: Discussionmentioning
confidence: 99%